EFFECTIVENESS OF PARTITION WATER BITTER MELON AGAINST DECREASE IN BLOOD SUGAR EXPERIMENTAL DIABETIC MALE RATS - Yudha, Dwi Widananta Yogi Indra; Suartha, Nyoman; Sudimantini, Luh Made (Buletin Veteriner Udayana, 2018)
The aims of this research are to find out the effectiveness of water partition Momordicia charantia fruit to the decrease blood glucose of experimental diabetic male rats ( Rattus norvegicus ). This research used twenty 3 months old male rats which were adapted for 2 weeks. Rat grouped into 4 groups namely the negative control (P0), only given food and drink alone; positive controls (P1), was given only feed, drink, and streptozotocin; EP group (P2), was given food, drink, streptozotocin, and extra bitter melon 2%; water partition group was given feed, drinking water and partitions streptozotocin 50 mg / kg body weight. Streptozotocin giving conducted on days 0, giving extract bitter melon and water partition conducted from day 3 to day 20. Measurement of glucose conducted on days -1, 0, 4, 11 and 18. The obtained data were evaluated using one-way ANOVA test. The results showed that water partition Momordicia charantia fruit could decrease blood glucose levels in a dose of 50 mg / kg of body weight significantly compared with the positive control.